Analysis of the Differences Between Female and Male Employment in Türkiye with Different Variables - Korkmaz, Murat; Yucel, Ali Serdar; Gumusdag, Hayrettin; Aytac, Ayhan; Duz, Ozan (Sciendo, 2024)
The research aims to analyze the differences between male and female employment in Turkey between 2007 and 2022. In this process, various variables are taken into account and the results are supported by TUIK (Turkish Statistical Institute) data. In this study, panel data of TUIK for the years 2007-2022 were used as the methodology. These data were analyzed using SPSS 22 and E-Views programs using Correlation, Anova, Independent Samples t test, Man-Whitney u test and Regression tests. At the end of the analysis, it was seen that there is a high degree of correlation between female and male employment and that there is a high level of difference in terms of employment in all female age groups. According to the regression analysis results, female employment grows by 0.28 units per year, while male employment grows by 0.11 units per year. This shows that female employment has been rising faster than male employment in recent years.
Keywords: Female; Male; Employment; Gender; Inequality; Education; Discrimination; C10; C51; J16; J21; K31